(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the influence of syntax on the formation of literary images in a work of literature. The article reveals various syntactical devices such as sentence length, inversion, anaphora, epiphora, parallelism, antithesis, which affect the perception of the text, convey mood, emotions, rhythm and dynamics of the narrative. The article also analyzes examples from classical literature, demonstrating how masters of the word use syntactical devices to create vivid, memorable images of characters, landscapes, atmosphere and events. The article will be useful for anyone interested in literary language and wanting to understand how to masterfully use syntactical devices to give their texts more expressiveness and artistic power.